Upper-limb force-time characteristics determine serve velocity in competition tennis players - Baiget, E.; Colomar, J.; Corbi, F. (International Journal of Sports Physiology and Performance, 2022)
Purpose: (1) To analyze the associations between serve velocity (SV) and various single-joint upper-limb isometric force-time curve parameters, (2) to develop a prediction model based on the relationship between these variables, and (3) to determine whether these factors are capable of discriminating between tennis players with different SV performances.